2012
DOI: 10.1007/s12262-012-0533-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute Biliary Pancreatitis: An Experience in a Tertiary Level Hospital of Nepal

Abstract: Acute Biliary Pancreatitis is one of the commonest forms of pancreatitis in Nepal. Controversies exist as to the most appropriate way of management of these cases. The present study was carried out to evaluate the management and outcome of Acute Biliary Pancreatitis cases in a tertiary level hospital of Nepal. A retrospective analysis of the patients managed with Acute Biliary Pancreatits was done. All patients admitted with the diagnosis of Acute Biliary Pancreatitis over a period of 2 years were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
7
10
3
Order By: Relevance
“…The commonest etiology of pancreatitis was alcohol induced (53.2%) followed by biliary pancreatitis (37.1%). Alcohol (59.34%) was similarly the most common cause of acute pancreatitis followed by gallstone (32.52%) in the study by Negi et al 8 Similar were the findings in the study by Manadhar et al 6 and Rao et al 12 Whereas, Gall stone disease was most common etiological factor seen in 40% cases followed by alcohol in 38% according to Raghuwanshi et al 11 Biliary tract disease (71.4% ) was the most common etiology in the study by Reid et al 7 The most common presentation was characteristic abdominal pain (100%) followed by nausea (83.9%), vomiting (66.1%), abdominal tenderness in (61.3%) and fever (2%) in the current study. Pain abdomen (100%) followed by vomiting (42.27%) were the common presentation in the study by Negi et al 8 , findings similar to ours.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The commonest etiology of pancreatitis was alcohol induced (53.2%) followed by biliary pancreatitis (37.1%). Alcohol (59.34%) was similarly the most common cause of acute pancreatitis followed by gallstone (32.52%) in the study by Negi et al 8 Similar were the findings in the study by Manadhar et al 6 and Rao et al 12 Whereas, Gall stone disease was most common etiological factor seen in 40% cases followed by alcohol in 38% according to Raghuwanshi et al 11 Biliary tract disease (71.4% ) was the most common etiology in the study by Reid et al 7 The most common presentation was characteristic abdominal pain (100%) followed by nausea (83.9%), vomiting (66.1%), abdominal tenderness in (61.3%) and fever (2%) in the current study. Pain abdomen (100%) followed by vomiting (42.27%) were the common presentation in the study by Negi et al 8 , findings similar to ours.…”
Section: Discussionsupporting
confidence: 76%
“…The majority of cases were in age groups of 41 -60 years and male predominance was observed in all age groups (M:F=2.3:1). In a previous study in Nepal by Manandhar et al 6 , the mean age of patients was almost similar, 45±10 years with male dominance. The male dominance in both these studies could be because of more alcohol consumption in males compare to females in Nepal.…”
Section: Discussionmentioning
confidence: 76%
“…These findings are consistent with those reported by Manadhar et al in 2013 reporting increase prevalence of pancreatitis among female sex in Nepalese population in 1:1.5 ratio. 6 Increase incidence of pancreatitis among Nepalese female population was also reported by Bohara et al 7 Mortality among patients admitted with hepatobiliary disease of medical cause was 54.16%, this is on consistent findings of Shellman RG et al who also found mortality of 64% in similar group of patients. 8 In 2012, Flood S et al performed a systemic review and found mortality of 40 to 50% among patients of alcoholic liver disease admitted in intensive care unit.…”
Section: Discussionsupporting
confidence: 73%
“…However, sensitivity and specificity decreased to 67%-78% in the course of acute pancreatitis because of the paralytic ileus [9].…”
Section: Discussionmentioning
confidence: 97%